Sikap Bahasa Siswa SMP dan SMA terhadap Pembelajaran Bahasa Inggris di Kota Bandar Lampung - Sudirman Sudirman; Huzairin Huzairin (Aksara: Jurnal Bahasa dan Sastra, 2017)
The objective of this study was to describe laguage attitude of junior and senior high school (SMP and SMA) students in learning English as a lesson at shools in Bandar Lampung. Since language attitude is a basic motor to motivation in learning language including English, it is of a worthy attention to know and describe it for the sake of teaching and learning English process. The population of this study was SMP and SMA students while the samples were a number of the students taken purposively. Accordingly, the samples were stratified sampling. Data were collected using questionaire with closed question items and analized using simple profile model. The result showed that SMP students` attitude toward native speaker, learning orientation, and motivation was higer than their attitude toward class and English teachers. Similarly, SMA students` attitude was high in learning orientation, followed by motivation of learning. The difference of attitude between SMP and SMA students was shown by the highest score on the attitude toward the importance of learning English in order to be appriciated if they have good ability in Englsh.Keywords: Attitude, Learning English, Motivation